Reviving the Atrial Switch: A Case Report of Successful Senning Procedure in a 13-Year-Old with Late-Presenting d-Transposition of the Great Arteries - Rido Mulawarman; Sonya Aprelladiva; Indira Kalyana Makes; Adnan Rhafif; Ahmad Yani Mansur; Ericko Ongko Joyo; Della Fergina; Ruth Sabathani Ayuningtyas; Hiradipta Ardining; Muhammad Adrin Aefiansyah; Sisca Natalia Siagian (The Indonesian Heart Association, 2026)
Background: d-Transposition of the Great Arteries with an Intact Ventricular Septum (d-TGA-IVS) is a severe congenital cardiac anomaly typically necessitating an Arterial Switch Operation (ASO) during the neonatal stage. In late presenters with a regressed Left Ventricle (LV), ASO becomes high-risk or infeasible, making atrial switch procedures such as the Senning procedure a potential salvage option, particularly in resource-limited settings. Case Illustration: We report a 13-year-old boy with lifelong cyanosis who developed progressive exertional dyspnea. Echocardiography and cardiac catheterization confirmed d-TGA-IVS with secundum atrial septal defect, severe Right Ventricular Hypertrophy (RVH), and preserved Pulmonary Vascular Resistance (PVR) (1.93 WU). Due to LV regression and the limited feasibility of late ASO, a Senning atrial switch was performed. Postoperative recovery was clinically stable, with oxygen saturation improving from 73% to 91%. Early postoperative echocardiography showed reduced systemic Right Ventricular (RV) function (Tricuspid Annular Plane Systolic Excursion [TAPSE] 7 mm), which subsequently improved on follow-up. Conclusion: The Senning procedure remains a valuable salvage option for very-late presenting d-TGA-IVS with favorable pulmonary hemodynamics when ASO is not feasible. This case underscores the importance of periodic reassessment of operability in patients initially deemed inoperable and highlights the need for lifelong follow-up to monitor systemic RV function, arrhythmia risk, and baffle integrity.